Heterotrophic cultivation of Ettlia sp. based on sequential hydrolysis of Helianthus tuberosus and algal residue. (1st May 2020) - Kim, Minsik; Cho, Jun Muk; Kim, Hee Su; Lee, Hansol; Oh, Hee-Mock; Chang, Yong Keun
Graphical abstract: Highlights: Hydrolyzed H. tuberosus replaced fructose in heterotrophic Ettlia sp. cultivation. Hydrolysates of algal residue replaced yeast extract as N source. Sequential hydrolysis was developed to utilize C and N sources simultaneously. Lipid productivity was enhanced with sequential hydrolysates medium. Abstract: Heterotrophic cultivation of microalgae results in substantial productivity but requires significant nutrient input. Alternative sources of major nutrients such as C and N should be carefully selected to make heterotrophic production of microalgal biomass feasible. In this study, Helianthus tuberosus and lipid-extracted algae (LEA) were hydrolyzed with sulfuric acid to grow Ettlia sp. YC001. Hydrolysis of H. tuberosus with 0.3 N of sulfuric acid resulted in fructose yield of 0.51 g g −1 and glucose yield of 0.14 g g −1 at 80 °C in 1 h. Proteolysis of algal residue with 2 N of sulfuric acid resulted in amino acid yield of 0.38 g g −1 at 110 °C in 24 h. To simplify the production of hydrolysates, the hydrolysis conditions were combined to establish a tailored sequential hydrolysis process. Then, simultaneous neutralization and salt removal of the hydrolysates were done with barium hydroxide. Consequently, cultivation of Ettlia sp. with the diluted sequential hydrolysate of H. tuberosus and LEA successfully achieved 5.90 g L −1 d −1 of biomass productivity and 1.42 g L −1 d −1 of lipid productivity with Ettlia sp.